(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Chronic gastritis is a disease characterized by chronic inflammation of the gastric mucosa with the gradual development of its atrophy, disorder of the secretory, motor and endocrine functions of the stomach. The most common cause is damage to the gastric mucosa by the bacterium Helicobacter pylori. Helicobacter inhabits the gastric mucosa, causing inflammation and damage. The source of infection is an infected person. It is believed that about 80% of cases of HG are associated with Helicobacter pylori.